Sikap Ibu Terhadap Pertanyaan Anak Tentang Seksualitas - Sri Lestari; Wisnu Sri Hertinjung (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2007)
Mother can give sexual education for their children continuously. Through it children could get attitude and moral values beside information related to. This research aimed to fin out mother’s attitude toward children questions about sexuality. Forty mothers as research subjects were taken from purposive nonrandom sampling procedure. They are whose having pre-teenage children.Data collected through recorded procedure. They are whose having mother-children communication situation.. Research show that mother attitude correspond to children query have 5 variations (1) giving explanation (51,07%); (2) feeling surprised and confused (17,86%); (3) asking children to stop asking (2,14%); (4) postponing answers with assumption that children will find the answers by their own. (12,14%) and (5) changing conversation topics (16,43%). Based on that findings, it is concluded that mothers willingness to give explanation on children question about sexuality indicate their readiness to communicate sexuality topics. Other attitudes indicate mother’s un-readiness to respond on children’s sexuality question. Keywords : mothers attitude, children question, sexuality